2023
DOI: 10.3389/fphy.2023.1120284
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution electric field and temperature distributions in positive streamers

Abstract: In this work, we aim to take a detailed experimental picture of the positive streamer. We apply optical emission spectroscopy to the first negative system (FNS, B2Σu+→X2Σg+) of N2+ and the second positive system (SPS, C3Πu → B3Πg) of N2. Large, centimeter wide, and highly reproducible streamers are created in pure nitrogen and synthetic air, at pressures ranging from 33 to 266 mbar. Direct time resolved spectral imaging of the space charge layer resulted in spatiotemporal maps of the calculated reduced electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The exception is to additionally modify the dependence of Paris et al [30] as suggested in [16,31,33,34]. Such modified curve was used for diagnostics of streamer or nanosecond pulsed discharges [17,35] and is well within the uncertainty interval discussed in [29,31]. To overcome the issue of the R(E/N ) dependence coming from the equilibrated steady-state Townsend discharge, the method may be developed and studied also in a time-dependent case by a theoretical means (see also [15]), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The exception is to additionally modify the dependence of Paris et al [30] as suggested in [16,31,33,34]. Such modified curve was used for diagnostics of streamer or nanosecond pulsed discharges [17,35] and is well within the uncertainty interval discussed in [29,31]. To overcome the issue of the R(E/N ) dependence coming from the equilibrated steady-state Townsend discharge, the method may be developed and studied also in a time-dependent case by a theoretical means (see also [15]), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The method of electric field determination via the first Townsend coefficient is affected by the presence of nitrogen metastable states. The method of FNS/SPS ratio, while successfully utilized for streamer discharges [6,54], is here at the limit of its applicability, apparently due to the impossibility of fully verifying all the underlying assumptions and the low electric field, which needs to be measured. Nevertheless, the overestimation of the electric field from the line ratio is comparable to the accuracy of the method estimated by the analysis of the molecular data (cross sections, lifetimes etc).…”
Section: Townsend Coefficient: Applicabilitymentioning
confidence: 99%